Factors associated with needle stick and sharp injuries among healthcare workers in Felege Hiwot Referral Hospital, Bahir Dar, Northwest Ethiopia: facility based cross-sectional survey - Walle, Lulie; Abebe, Emebet; Tsegaye, Medihanit; Franco, Hanna; Birhanu, Dereje; Azage, Muluken (International Journal of Infection Control, 2013)
Needle stick and sharp injuries are occupational health hazards to healthcare workers. Every day they are exposed to deadly pathogens through contaminated needle and other sharps injuries. The aim of this study was to assess the prevalence and factors associated with needle stick and sharp injuries among healthcare workers in Felege Hiwot Referral Hospital. Facility based cross-sectional survey was conducted from 1-5 July 2012, using questionnaire. All healthcare workers contacted in the study period were included. Data was analyzed using SPSS version 16.0. Binary logistic regression was used to identify factors associated with needle stick and sharp injuries. From the total 332 healthcare workers enrolled, 216 (65.1%) were females. Nearly 2/3rd were diploma holders, and Nurse by profession. Hundred three (31.0%) had needle stick and sharp injury at least once in the previous 12 months. Three fourth of the injuries was due to needle stick. Those whose monthly income was >=1000.00Eth Birr, satisfied on their job, and worked in waste handling unit were 4.1, 2.8, and 4.1 times more injured than their counterparts respectively (Adjusted Odds ratio [AOR] =4.1, 95% Confidence Interval [CI] 1.27-13.14, AOR=2.78, 95% CI 1.01-7.63, and AOR=4.1, 95% CI 1.27-13.14). Those who worked in maternity unit were 80% less injured than those who worked in Emergency units (AOR= 0.20, 95% CI 0.053-0.78). Nearly 1/3rd of participants had needle stick and sharp injury at least once in the previous year. Suboptimal practices and behaviours that put them at risk to the injury were identified. Authorities should give on job training, and regular supportive supervision. Further research is needed to determine the incidence of the injury, and the type of disease they would acquire.